Processamento de peças em materiais compósitos para o projeto BAJA SAE - Tafarello, Ivylin Giovanna [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The weight of a vehicle has always been considered an extreme important factor, because it interferes in the performance, steering, consume, environmental impact, wear of components, among the others. Because of the new demand, consume reduction aim and gases emission increased the necessity to manufacture lighter vehicles, guaranteeing the complying with the gas emission international law. Besides the legal demand, the low weight will certainly be essential for the competitiveness for the next generation of vehicles. It is with this thinking the composite materials have been introduced in the automobilist industry, because those materials show an excellent relation of strength/weight, providing a reduction of consume and the increase of load capacity. Those factors justify the increase of interest of industry and the necessity of optimization of those materials and of their process. For this research, the field of application will be the Baja SAE Project, a project that is fully developed by engineering students, where they build a prototype single seat, off-road category, for use on hilly slopes with obstacle. This research aims to study two key components of the prototype are made of composite materials, analyzing all the processing. In addition, there is the analysis of the viability of this production parts to a Baja SAE vehicle, in order to increase their performance and reduce their weight without reducing the safety and robustness of the prototype. It was possible to achieve weight reduction of the steering subsystem with manufacturing the flywheel hybrid composite (carbon/glass) and the replacement of SAE 1010 steel by hybrid composite (carbon/aramid) in CVT box. The importance of this study is to obtain a good project for the vehicle of technical and scientific manner, contributing to the know-how to the team and providing a basis for optimization for upcoming projects

O peso de um veículo sempre foi considerado um fator de extrema importância, pois influencia no desempenho, dirigibilidade, consumo, impacto ambiental, desgaste de componentes, entre outros. Com as novas exigências, metas de redução de consumo e de emissões de gases aumentaram a necessidade de fabricarem-se veículos mais leves, garantindo o cumprimento das legislações internacionais de emissões. Além das exigências legais, o baixo peso certamente será fundamental para a competitividade das próximas gerações de veículos. É com essa mentalidade que os materiais compósitos têm sido introduzidos na indústria automobilística, pois apresentam excelente relação resistência/peso, significando consequentemente uma redução de consumo e aumento da capacidade de carga. Esses fatores justificam o crescente interesse demonstrado pela indústria e a necessidade de otimização desses materiais e de seus processos. Para este trabalho, o campo de aplicação será o projeto Baja SAE, que é um projeto totalmente desenvolvido por estudantes de engenharia, onde constroem um protótipo monoposto, na categoria fora de estrada, para a utilização em pistas acidentadas, com obstáculo. Esta pesquisa visa o estudo de duas peças fundamentais do protótipo que são feitas de materiais compósitos, analisando todo o processamento. Além disso, tem-se a análise da viabilidade de aplicação desse sistema de produção de peças a um veículo Baja SAE, com a finalidade de aumentar seu desempenho e reduzir seu peso, sem reduzir a segurança e a robustez do protótipo. Foi possível alcançar a redução de peso do subsistema de direção com a fabricação do volante em compósito híbrido (carbono/vidro) e a substituição do Aço SAE 1010 pelo compósito híbrido (carbono/aramida) na caixa de proteção do CVT. A importância desse estudo está na obtenção de um bom projeto ... (Resumo completo,clicar acesso eletrônico abaixo)
Keywords: Materiais compostos; Indústria automobilística; Fibras de carbono; Resinas epoxi; Laminação (Metalurgia); Analise termica; Viscosimetro; Calorimetria; Composite materials